Metacognitive Learning Approach in Affecting Students’ Self-Regulated Learning in Writing Course - Abdul Halim; Sofia Ulfa Eka Hadiyanti (AL-ISHLAH: Jurnal Pendidikan, 2021)
The research aimed to investigate the effect of metacognitive instruction on students' self-regulated learning (SRL) writing for Indonesian EFL students to have appropriate grammar and meaningful learning experiences. The methodology used was a quasi-experimental design. The research participants were 50 students from the University of Muhammadiyah East Kalimantan (UMKT) English department who took a writing course. The participants were divided into the experimental group that was taught with metacognitive instruction. In contrast, although the same teacher taught the control group and had similar learning materials, the teacher did not use metacognitive instruction. The data was taken through pre-test and post-test and analyzed through independent t-test with statistics tool SPSS. The results showed that the experimental group has a higher SRL score with significant results in overall score even though there is one component that is different from previous studies, namely knowledge of cognition. Some suggestions were proposed.